The Utility of Hypochromic Markers in the Detection of Latent Iron Deficiency in Women in their First Trimester of Pregnancy - Haliz Salman Sulaiman; Firdous Hussein Ahmed; Nasir Al-Allawi (Advanced Medical Journal)
Background and Objectives: While iron deficiency anemia is a documented common problem in pregnancy, there is limited information on latent iron deficiency. Accordingly, we aimed to determine the frequency of the latter in the first trimester of pregnancy and assess the utility of new hypochromic markers in screening for it.